A Gloss to the Judgment of the Appellate Court in Warsaw of 28 May 2013 (VI Aca 785/13) - Witczak, Hanna (Review of European and Comparative Law, 2022)
In the glossed judgement, the Appellate Court examined the possibility of declaring the respondent unworthy of succession should he have committed the offence of avoidance of the duty of maintenance of the testator (Article 209 PC) or the offence of abandonment of the testator (Article 210 PC). The court’s considerations were purely hypothetical, as in the course of the proceedings, it was not proven whether the heir had actually committed these offences. The court allowed the recognition of the heir as unworthy if he had committed the offence of persistent avoidance of the duty of maintenance, but only if it could be proven. The court’s position raises certain doubts. Any conduct that violates familial nexus, in particular, should be verified for the existence of grounds for exclusion from succession, since this bond, in the legal sense, has its source in the relationship of marriage, consanguinity, and affinity, and these determine the legal title to inheritance. In particular, it is not understandable why persistent failure to fulfil family obligations, even if it is not an offence that a civil tribunal could additionally qualify as serious, does not actually produce legal consequences for the parent if the other party to the family relationship is a minor. It seems that wherever we are confronted with malicious and intentional failure to perform family duties, it should be assumed, provided that the statutory criteria of this specific type of offence are met, that in abstracto a serious offence has taken place.